Mobility extra situ – The Cosmopolitical Aesthetics of Tania Ruiz Gutierrez' Elsewhere/Annorstädes/Ailleurs. (14th March 2016) - Hellström Reimer, Maria
Abstract: In discussing a major public video installation, Elsewhere/Annorstädes/Ailleurs by Tania Ruiz Gutierrez, the present article seeks to address what is referred to here as 'mobility ex situ ' – the unsettling aspects of a mobility culture that is both ubiquitous and at the same time exorbitant, never simply 'in place'. Commissioned for one of the stations along the Øresund Link between Denmark and Sweden, this world-embracing cinematic montage is an integrated part of an expansive connectivity infrastructure. Yet, while providing site-specific motion captures of a translocational world, the work not only actualises a radically transformed sense of presence. Randomised and disjointed, the flow of imagery also draws attention to the territorial incoherencies and asymmetries of a mobility culture, which, despite increased site sensitivity, does not manage to shake off its constitutive 'elsewheres'. The artwork thus provides an opportunity to unfold the 'mobility script' from an aesthetic – but also political – point of view, and this in three consecutive steps: the first, an introductory presentation of the art work as situational stammering; the second, a critical reflection through the work on nomadic or dispersed geographies; and the third, a discussion of the work as an expression of a cosmopolitical aesthetics.